Pagtatagpo sa kabilang dulo panitikang testimonial ng desaparecidos - Rodriguez, Rommel B.; Tolentino, Rolando B.; Batnag, Aurora E.; Mercado, Emil; Padilla, Jennifer T. ([publisher not identified], 2009)
Collection of poems, letters and testimonials of the families of victims of enforced disappearances.